Surface mine design using intelligent computer techniques - Schofield, Damian (1992)
Surface mine planning involves the results of algorithmic numerical calculations being used by engineers to make informed decisions relating to the design. The Department of Mining Engineering at the Unversity of Nottingham has in the past been involved in developing modular algorithmic packages. The emphasis of the computer research has now altered. Smaller specialised systems are now being developed to cover individual aspects of the design process. Artificial intelligence techniques are being introduced into the mining environment to solve the planning problems often associated with the large amounts of uncertain information needed by the engineer. This thesis is concerned with the development of MINDER, a decision support system capable of assisting the mine planner in the complex task of optimum surface mining equipment selection. An expert system shell has been used to create a series of individual application modules, each containing a multi-level knowledge base structure. An information handling system has been developed which is capable of storing consultation information and transfering it between knowledge bases and between application modules. Once an effective method of information handling had been achieved the flow of control between the system knowledge bases was rapid and followed complex inferencing routes.